STN1 facilitates metastasis by promoting transcription of EMT-activator ZEB1 in pancreatic cancer - Di Dong; Zhe Zhou; Minglu Zhu; Zhiyuan Hou; Mo Chen; Jingjing Gong; Xuyang Zhao; Aohui Yan; Hui Liang; Yuxin Yin (Nature Communications)
Abstract Pancreatic ductal adenocarcinoma (PDAC) poses a serious clinical challenge, demanding further exploration of its pathogenesis and therapeutic targets for metastasis, the main cause of mortality. Here, we identify STN1, a CST complex member crucial for maintaining telomere lengths and genome stability, as a key factor in promoting PDAC metastasis. Elevated STN1 levels correlate with poor patient survival, with oncogenic protein HOXB7 as an upstream transcription factor regulating STN1. Utilizing multiple PDAC experimental models, we discover STN1’s role in promoting metastasis by functioning as an upstream factor in epithelial-mesenchymal transition (EMT). Our mechanistic evidence suggests that during transcription, STN1 binds to structurally displaced single-stranded DNA flanking the R-loop, recruiting STAT3 to activate ZEB1 transcription independent of its known telomere maintenance function. Notably, STAT3 inhibitors show enhanced efficiency in restraining metastatic potential in STN1-overexpressed PDAC cells, offering a potential therapeutic avenue for targeting metastasis in STN1-overexpressed PDAC patients facing an unfavorable prognosis.